Does Market Structure Affect the Immediacy of Stock Price Responses to News? - Masulis, Ronald W.; Shivakumar, Lakshmanan (Journal of Financial and Quantitative Analysis, 2002)
Ronald W. Masulis, Lakshmanan Shivakumar, Does Market Structure Affect the Immediacy of Stock Price Responses to News?, The Journal of Financial and Quantitative Analysis, Vol. 37, No. 4 (Dec., 2002), pp. 617-648